Giustizia, uguaglianza e differenza Una guida alla lettura della filosofia politica contemporanea - Cini, Lorenzo (Studi e saggi, 2012)
At least until the beginning of the 1990s, when the paradigm of recognition seemed to supplant the paradigm of redistributive justice theories, all the biggest contemporary political theories attempted to single out injustice in some form of inequality and tried in various ways to make individuals equal within a particular space for interpersonal comparison: whether this be the space of fundamental freedoms, income, wealth, conditions for self-respect, well-being, chances of well-being or capabilities. The objective of this work is to rebuild the main notions of equality and justice which have emerged from the contemporary philosophical-political debate and, at the same time, account for the critical theories that they have inspired, from the theories in which the language of difference adds to or surpasses the language of equality, to the paradigms located radically beyond all those regulatory positions which more or less explicitly arise from the liberal tradition, such as the paradigm of biopolitics, and that of cognitive capitalism.